DRACAENA JIEWHOEI (ASPARAGACEAE), A NEW ENDEMIC SPECIES FROM SUMATRA, INDONESIA - G. G. Hambali; Diah Sulistiarini; Rugayah Rugayah (Research Center for Biology, 2020)
HAMBALI, G. G., SULISTIARINI, D. & RUGAYAH. 2020. Dracaena jiewhoei (Asparagaceae), a new endemic species from Sumatra, Indonesia. Reinwardtia 19(2): 75‒79. ‒‒ Dracaena jiewhoei Hambali, Sulistiarini & Rugayah, a new endemic species from Muara Emat, Batang Merangin, Jambi, Sumatra, Indonesia is described and illustrated. It is genetically related to Dracaena cantleyi Baker but differs substantially in a range of morphological and its growth pattern characteristics.